Dampak kompetensi dan kompensasi terhadap motivasi kerja dan pengaruhnya terhadap Kinerja Pegawai pada Pondok Pesantren Riyadlul Jannah Mojokerto - Didi Sudira (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2022)
The aims of this study are to: 1) Analyze competence on work motivation. 2) Analyzing the effect of compensation on work motivation. 3) Analyzing the effect of competence on employee performance. 4) Analyzing the effect of compensation on employee performance. 5) Analyzing the effect of employee performance on work motivation. 6) Analyzing the influence of competence indirectly on employee performance through work motivation. 7) Analyzing the effect of indirect compensation on employee performance through work motivation. The population of this study was 38 people, so the sampling method was using the census technique. Where all members of the population are sampled. data analysis tool using SmartPLS software version 3.3.7. From the results of the study, it can be concluded as follows: 1) Competence has a significant effect on Motivation 2) Compensation has no effect on Motivation 3) Competence has a significant effect on Performance 4) Compensation has no effect on Performance 5) Motivation has a significant effect on Performance 6) Competence has an indirect effect on Performance through Motivation 7) Compensation has no indirect effect on Performance through Motivation.